Work Motivation as a Mediator of Compensation and Training Effects on Employee Productivity: A Multi-Plant Study at PT Tri Centrum Fortuna - Jajang Saep; Pras Rendy; Gurawan Dayona; Kartika Nuradina; Andhika Mochamad Siddiq (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examines the role of work motivation in mediating the relationship between compensation, training, and employee productivity at PT Tri Centrum Fortuna Purwakarta and Karawang plants. The research was conducted due to the increasing need to improve employee productivity in the automotive manufacturing industry. A quantitative explanatory approach was employed using Structural Equation Modeling with AMOS (SEM-AMOS). Data were collected through Likert-scale questionnaires distributed to 279 employees consisting of 126 employees from Purwakarta and 153 employees from Karawang. The findings reveal that compensation has no significant effect on work motivation or employee productivity at both plants. In contrast, training has a positive and significant effect on work motivation at both locations, while its effect on productivity is significant only at the Karawang plant. Work motivation significantly improves employee productivity at both plants. Furthermore, work motivation fully mediates the relationship between compensation and productivity and partially mediates the relationship between training and productivity. The study concludes that training and work motivation are more influential than compensation in improving employee productivity. Therefore, companies should strengthen employee training programs and motivational strategies to enhance productivity and organizational performance.